Aqueous extracts of Propolis and Miswak as topical medicament to improve post- operative outcome after surgical removal of impacted lower third molar - Faiz A Al-Sultan1; Layla A Mustafa; Ali I Al-Niaimi (University of Mosul, College of Dentistry, 2006)
Aim: To asses the effects of topical application of aqueous extract of either Propolis or Miswak on the post-operative outcomes in relation to the duration of operation after surgical removal of lower third molar was performed. Material and Methods: A total of 97 patients participated and distributed randomly into 3 groups according to the medicament applied into the extraction socket: Group I, in which 5% aqueous solution of propolis extract used; group II, in which 10% aqueous solution of Miswak extract used; and group III, in which distilled water used (control group). Results: A significant improvement in post-operative outcome at 3rd day in both group I and II comparing to group III was observed. No significant difference noticed at 1st day and 6th day. Assessment of dry socket showed no significant difference in between the three study groups. However, when assessment performed in relation with operation time, a significant difference noticed in between the three study groups with high incidence of dry socket reported in operation take longer than 30 minutes in the three study groups. Conclusion: Aqueous extract of Miswak and Propolis as a topical medicament following lower third molar extraction had a slight reducing effect on the severity of post-operative complications.